The Malay literacy movement as a best practice in curriculum development in elementary schools - Sriyantini; Dhiniaty Gularso (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
The Malay Literacy Movement is a locally developed curriculum innovation at SDN 010 Bintan Utara to strengthen literacy skills while instilling character values and a love for Malay culture in elementary school students. This study aims to describe the implementation of the Malay Literacy Movement, analyze improvements in students' literacy and character through classroom action research, and identify the involvement of schools, families, and communities in supporting the sustainability of local culture-based literacy programs. The study used a Classroom Action Research (CAR) design, conducted in two cycles, with the following stages: planning, action implementation, observation, and reflection. The research subjects included all students in grades I-VI at SDN 010 Bintan Utara. Data were collected through observation of literacy activities, analysis of student work, documentation, and teacher reflection, and were then analyzed qualitatively, supported by percentage data to reinforce the results of each cycle. The results showed an increase in student literacy achievement from cycle I to cycle II. In cycle I, around 65% of students wrote pantuns with the correct structure and rhyme, and this increased to around 78% in cycle II. Students' ability to retell Malay fairy tales coherently and communicatively increased from around 60% in cycle I to around 72% in cycle II. In addition, students' active participation and confidence in literacy activities increased in cycle II. These findings indicate that the Malay Literacy Movement has the potential to serve as a model for developing a culture-based curriculum in elementary schools